School Principal’s Strategy in Developing Teacher’s Professional Competencies to Improve Educational Quality - Riyany, Evy; Harapan, Edi; Tahrun, Tahrun (Yayasan Sembilan Pemuda Indonesia, 2020)
This study identified the principal's strategy in developing teacher’s professional competence. This research used a qualitative approach with descriptive methods. Data collection techniques are carried out through interviews, observation and documentation. The research subjects were the principal and teachers of SD Negeri 1 Kota Prabumulih. The results showed that: (1) in order to improve and develop the professional competence of teachers in SD Negeri 1 Kota Prabumulih, the head seems to implement and implement a strategy in the form of